2020
DOI: 10.3390/sym12091464
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness and Stratification of Single-Valued Neutrosophic Topological Spaces

Abstract: This paper aims to introduce the notion of r-single-valued neutrosophic connected sets in single-valued neutrosophic topological spaces, which is considered as a generalization of r-connected sets in Šostak’s sense and r-connected sets in intuitionistic fuzzy topological spaces. In addition, it introduces the concept of r-single-valued neutrosophic separated and obtains some of its basic properties. It also tries to show that every r-single-valued neutrosophic component in single-valued neutrosophic topologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Others as Wang et al [4] defined the single-valued neutrosophic set concept. In (2020, 2021) Saber et al [5][6][7][8][9][10][11] introduced and studied the concepts of single-valued neutrosophic ideal, single-valued neutrosophic ideal open local function, connectedness in single-valued neutrosophic topological spaces (£, ˜ σ , ˜ ς , ˜ δ ) and compactness in single-valued neutrosophic ideal topological spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Others as Wang et al [4] defined the single-valued neutrosophic set concept. In (2020, 2021) Saber et al [5][6][7][8][9][10][11] introduced and studied the concepts of single-valued neutrosophic ideal, single-valued neutrosophic ideal open local function, connectedness in single-valued neutrosophic topological spaces (£, ˜ σ , ˜ ς , ˜ δ ) and compactness in single-valued neutrosophic ideal topological spaces.…”
Section: Introductionmentioning
confidence: 99%
“…We must state that this subject has been researched by physicists [7,[10][11][12][13] as well as by others. El-Naschie has shown that the notion of fuzzy topology in Ŝostak sense has very important applications in quantum particle physics especially about both string theory and ε (∞) theory [8,9,12,15,16] and also Saber et al [30][31][32][33][34][35][36][37][38][39] who familiarized the concepts of single-valued neutrosophic ideal open local function and single-valued neutrosophic topological space. In this paper, we give a decomposition of fuzzy continuity, fuzzy ideal continuity and fuzzy ideal α-continuity, and we obtain several characterizations of fuzzy α-I-continuous functions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Kim et al [5,6] inspected the single valued neutrosophic relations (SVNRs) and symmetric closure of SVNR, respectively. Recently, Saber et al [7][8][9] introduced the concepts of single-valued neutrosophic ideal open local function and single-valued neutrosophic topological space. Many of their applications appear in the studies of Das et al [10].…”
Section: Introductionmentioning
confidence: 99%